Impacto del comercio electrónico en la comercialización de ruanas boyacenses internacionalmente (2021)
What will be presented in this work is the analysis of the impact of the implementation of e-commerce on the commercialization of Boyacians internationally, taking into account characteristics, variables and possible factors that may favor or affect such implementation. The methodology used for the preparation of the document was descriptive in nature, because information was collected from different academic databases, as well as several government agencies and other digital resources such as articles or news.